The Role of Teachers in State Defense Efforts - Azizah, Nandin Ainnur (CV. Rayyan Dwi Bharata, 2022)
State defense is the attitude and actions of citizens based on love for the homeland, awareness of the nation and state, belief in Pancasila as the ideology of the nation and state, willingness to sacrifice in order to face every threat, challenge, obstacle and disturbance (ATHG) both coming from within and from outside the country. outside. The role of the teacher as an agent of change (agent of change) in realizing citizens who have awareness of the nation and state to defend the country with patriotic behavior which is implemented through Fostering State Defense Awareness by instilling the basic values of State Defense in the scope of Education.